Utilization of Video-Based Teaching Materials in the Subject of Fiqih for Grade VIII Students at MTsN 2 Sidenreng Rappang - Ibrahim; Buhaerah; Abd. Halik; Muhammad Saleh; Usman (Universitas Muhammadiyah Palu, 2024)
This discusses the utilization of video-based teaching materials in the Fiqih subject for Grade VIII students at MTsN 2 Sidenreng Rappang. The research aims to determine the utilization of video-based teaching materials in the Fiqih subject for Grade VIII students at MTsN 2 Sidenreng Rappang. This research employed a qualitative research design, specifically field research conducted directly at the school through observation, interviews, and documentary studies to obtain clear and representative data. The results of the research indicate: (1) The use of video media at MTsN 2 Sidenreng, Lakessi Village, Maritengngae Subdistrict, Sidenreng Rappang Regency, has been in place for several years, starting from the year 2011 with the introduction of liquid crystal display (LCD), and in 2021, the first appearance of a Smart TV as a tool for video playback utilized by teachers at MTsN 2 Sidenreng Rappang in the classroom, particularly in Fiqih lessons where teachers use video media to help students understand the material on almsgiving, grants, and gifts. (2) The learning process, especially in the Fiqih subject, allows students to easily utilize video media, which can be replayed both at school and at home to achieve satisfactory grades, as students are assigned practice tasks at home. (3) The teaching process involves the use of videos created by teachers at MTsN 2 Sidenreng Rappang. Students are given the opportunity to use videos available on the internet or YouTube related to the Fiqih material being taught.